Variation in protein and amino acids content among landraces of common bean (Phaseolus vulgaris L.) - Flores-Sosa, Ángel Ramón; Aquino-Bolaños, Elia Nora; Cardador-Martínez, Anaberta; Chávez-Servia, José Luis; Vera-Guzmán, Araceli Minerva; Carrillo-Rodríguez, José Cruz; Jiménez, Jimena Esther Alba (Emirates Journal of Food and Agriculture, 2020)
Native bean populations (Phaseolus vulgaris L.) provide bioactive and nutrient compounds; however, their amino acid profiles are unknown. Therefore, the aim of this study is to evaluate the protein content and amino acid profile of 46 native bean populations cultivated by small farmers in Oaxaca, Mexico, and compare them with that of commercial beans. Through high-performance liquid chromatography (HPLC), 16 amino acids were identified and quantified in all samples. The region of origin influenced the concentrations of amino acids. The Santa Lucia Miahuatlan populations stood out for their high content of isoleucine, threonine, methionine, arginine, serine, alanine, tyrosine, and cysteine. Amino acid content showed high variability among the populations; accessions labeled as FSLM22, FSLM27, FSLM28, and FSLM32 were enriched in aliphatic, hydroxylated, aromatic, acidic, and basic amino acids, while the FSLM14, FSLM17, and FSLM18 populations had the highest concentrations of sulfur amino acids. The FSLM01, FSLM22, FSLM27, FSLM28, FSLM30, and FSLM32 populations frequently displayed the highest concentrations of essential amino acids. The findings show that samples of native populations are highly variable in amino acid content due to the genetic characteristics of cultivated beans, environmental and agroecological influences, and crop management by farmers. The beans populations stood out can be used for direct use or a basis for the initiation of a breeding program.